Efeito da fritura sobre o valor nutritivo do camarão Pitu (Macrobrachium acanthurus Wiegman, 1836) do complexo Estuarino Lagunar Mundaú/Manguaba-AL - Simon, Sarah Janaina Gurgel Bechtinger (2010)
The crustaceans are noted for their great commercial interesting and acceptance into the consumer market. However, besides showing lipid fraction with polyunsaturaded fat acids, they are suffering cooking methods, such as frying, can favor the oxidation of these compounds and production of cholesterol oxides cytotoxic, teratogenic and mutagenic. In the present study, reviewed issues involved with frying process in fish, focused on different chemical changes that occurred in oil and food, as well as nutritional implications resulted from this culinary procedure. Therefore, considering the lack of information about the chemical composition of the “pitu” prawn (Macrobrachium acanthurus) from the Estuary Lagoon Complex Mundaú/Manguaba-Alagoas, studied in this work the frying effect on its nutritional value. It was determined in the in nature and fried prawn, the proximate composition, caloric value, fatty acid profile, cholesterol and oxides of cholesterol. The results obtained from in nature and fried pitu, were respectively, for moisture (73.59% and 67.47%), ash (1.31% and 1.47%), protein (23.56% and 28.80 %), carbohydrates (0.76% and 0.70%), lipids (1.58% and 2.23%), calories (117.20 kcal/100g and 160.20 kcal/100g), fatty acids (polyunsaturated 33.03% and 54.72%, omega-3 15.67% and 8.79% and omega-6 17.36% and 45.93%), cholesterol (102.89 mg/100 g and 137.11 mg / 100g) and oxides (7-ketocholesterol 0.01 g / g and 0.02 g / g Triol 0.81 g / g and 0.73 g / g). Concluded that “pitu” prawn has a high nutritional value and it’s a good source of essential fatty acids, but the frying leads to significant changes in its proximate composition specially in their lipid profile, is not this cooking method the most indicated for a nutritionally balanced diet with this food.